EP977 Impact of timing of cytoreductive surgery (CRS) on epithelial ovarian cancer (EOC), primary peritoneal carcinomatosis (PPC), and fallopian tube cancer (FTC) at american university of beirut medical center (AUBMC). (1st November 2019) - Seoud, M; El Housheimi, A; Jaafar, I; Hamed, K; Jamali, F; Abdallah, R; Khalil, A
Abstract : Introduction/Background: To study the impact of timing of CRS weather done at diagnosis or following neoadjuvant chemotherapy(NACT) on progression free(PFS) and overall survival(OS) of patients with advanced EOC between 1997–2017 at AUBMC. Decision to do primary(PDS) or interval debulking surgery(IDS) is based on factors that help determine the probability to achieve complete debulking (Stage, Tumor markers, tumor burden on imaging, clinical and performance status). Methodology: A retrospective review of the impact of PDS versus NACT followed by IDS on PFS and OS. Results: Of 300 patients with EOC, PPC and FTC, 220 were found to have advanced epithelial cancer (stage IIIB, IIIC and IV). 63% had interval debulking surgery (IDS) while 37% had primary debulking (PDS). Results are shown in table 1 . Conclusion: Timing of the CRS (PDS vs. IDS) significantly impacts PFS but not OS in stage IIIC but not IV EOC. This difference in survival is explained by the higher tumor burden, higher morbidity, and worse performance status of patients operated in the interval setting. Disclosure: Nothing to disclose.